REGULATION OF THE LEGALITY OF MICRO, SMALL AND MEDIUM ENTERPRISES THROUGH THE ONLINE SINGLE SUBMISSION SYSTEM TO INCREASE COMPETITIVENESS - Amin Purnawan; Siti Ummu Adillah (Jurnal Pembaharuan Hukum, 2020)
The purpose of this paper is to review the regulation of the legality of micro, small, and medium enterprises (MSMEs) through the Online Single Submission System (OSS) to increase competitiveness, as well as to analyze barriers and solutions. The research method used an empirical juridical approach, the collected data were analyzed by descriptive analysis. The results showed that the problematic implementation of the regulation of MSME business legality registration through the OSS System was mainly due to the lack of socialization and education to MSME entrepreneurs regarding the obligation to register permits through OSS. This affects the compliance of MSMEs in processing their business permits. The solutions that need to be done include increasing the socialization of Integrated Electronic Business Licensing Services/Online Single Submission. MSME players need to be empowered through human resource development, capital support, production and productivity, business protection, partnership development, business networks and marketing as well as business legality, especially registration of business licenses through the Integrated Electronic Business Licensing Service.